Energy-Harvesting Cooperative NOMA in IOT Networks - Mohammad Alkhawatrah (Modelling and Simulation in Engineering)
Buffer-aided cooperative nonorthogonal multiple access (NOMA) improves the effectiveness of the spectral by allowing more than one user to share the same resources to realize massive connectivity. This is notably attractive in the fifth generation (5G) and beyond systems, where a massive number of connections are essential such as the Internet of Things (IoT). Wireless-powered communication through energy harvesting is another 5G promising solution for the future massively dense networks. To sufficiently utilize energy harvesting in a buffer-aided cooperative NOMA network, the relay selection rule must consider the energy level of the selected relay in addition to its data content to avoid an outage. This paper proposes a relay selection rule for energy-harvesting buffer-aided cooperative NOMA networks. The proposed relay selection scheme considers the state of both the data buffer and the energy buffer. The simulations show that the proposed selection rule has improved the network outage probability and throughput as well. This enhancement is kept with changing the number of relays. The results also show that the impact of changing the energy buffer size is crucial, and the larger, the better. Furthermore, making the source transmitting power larger than the relay transmitting power is beneficial, especially with large enough energy buffer sizes.